KUALITAS KEPEMIMPINAN YUSUF BERDASARKAN KEJADIAN 39:1-23 BAGI KEPEMIMPINAN DIINDONESIA - David Ming (Sekolah Tinggi Teologi Duta Panisal, 2021)
Christian leadership that has the burden of a heart to prosper humanity, who always longs to give the best for God, and for all God's creatures, are wholly responsible to God in carrying out their duties and functions before God. Willing to sacrifice his life for the Glory of the Name of God, missionary-minded worldwide, is a leader who truly responds to the challenges amidst the pandemic COVID 19 epidemic in the world. For this reason, a discourse arose for writing a scientific work entitled: THE QUALITY OF CHRISTIAN LEADERSHIP BASED ON EVENTS 39; 1-23 BY THE PANDEMICCOVID SITUATION 19. Actually, instinctively, everyone has the talent to be a leader, but many do not realize, except those who have the desire (passion), prepare yourself to be a leader. The results of this writing study indicate that the dominant indicators that shape the quality of Christian Leadership based on Genesis 39: 1–23 are Indicators of High Integrity (X1). The indicators of Having High Integrity (X1) are very much determined by the indicators of Having Divine Authority (X2) and Indicators of Having a Wise Heart (X3). It is these indicators that will help leaders to maintain the quality of their faith in the midst of the pandemic covid 19.